KEBIJAKAN PENGELOLAN PASAR MODERN PERSPEKTIF HUKUM ISLAM (Studi Terhadap Peraturan Daerah Kota Palangka Raya Nomor 04 Tahun 2007 tentang Pengelolan Pasar Modern) - Muzalifah Muzalifah (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2016)
The Government regulation of Palangkaraya City in the form of Regional Regulation (Perda) Palangkaraya Number 04 Year 2007 on the Management of Modern Market need special attention. This is because the growth of modern markets in Palangkaraya in recent years has increased very high. This is compounded by how modern market participants who dared to operate before the operational permit issued. From the explanation, the purpose of this paper is to analyze how the management of a modern market in Palangkaraya perspective of Islamic law and the impact of regulation (Perda) on the management of the modern market for traditional market players. In order to achieve these objectives maximally, so this study used qualitative descriptive method, with a normative approach. The results indicate that the regulations (Perda) that have been made by the Government City of Palangkaraya is in line with Islamic law based on the concept of the rule on the basis of fiqh with benefit. Nevertheless, it needs to be replicated again in several articles, because it is irrelevant to the economic conditions in the Palangkaraya City particularly. In addition, it also shows the adverse implications for the existence of traditional markets.